Types, Prevalence, and Infection Rate of Ectoparasites on Dumbo Catfish (Clarias gariepinus): (Jenis, Prevalensi, an Tingkat Serangan Ektoparasit Pada Ikan Lele Dumbo (Clarias Gariepinus) - Rizky Baninta Ekaputri; Rosa, Emantis; Pratami, Gina Dania; Sumardi, Sumardi (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
Catfish (Clarias gariepinus) is a fish that is cultivated for human consumption. The success rate of cultivation is influenced by many factors, including the presence or absence of parasitic infections in cultivated fish. This study aims to determine the type, prevalence, and level of ectoparasite attacks on Dumbo Catfish in the Rajabasa Raya fishing pond, Bandar Lampung. The ectoparasites were taken using the method of scraping mucus and staining the ectoparasites on the surface of the fish's body, and then identified. The prevalence rate is determined using the Kabata prevalence formula. The results showed that two types of ectoparasites were found, namely Dactylogyrus sp. with the highest prevalence of 100% (infection rate is always), and Gyrodactylus sp. with the highest prevalence of 80%. (infection rate is common).